PENGARUH ONLINE CUSTOMER REVIEW, DISKON, DAN LIVE STREAMING TERHADAP KEPUTUSAN PEMBELIAN (SURVEI TERHADAP PENGGUNA E-COMMERCE TOKOPEDIA DI SURAKARTA) - Devin Yanuar Hardiyanto; Retno Susanti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
. This research aims to analyze the significance of the influence of online customer reviews, discounts and live streaming on Tokopedia e-commerce purchasing decisions in Surakarta. The types of data used are quantitative data and qualitative data. The data sources in this research are primary and secondary data. The population in this study is the unknown number of Tokopedia e-commerce users. The sampling method is purposive sampling or sampling with certain characteristics with a sample size of 100 people. The data analysis methods used are descriptive analysis, multiple linear regression analysis, t test, F test, and coefficient of determination test (R2) The questionnaire has been tested for validity and reliability, the results are valid and reliable, and meets the classical assumption test. The results of this research using multiple linear regression analysis show that online customer reviews, discounts, and live streaming have a significant influence on purchasing decisions for Tokopedia e-commerce purchases in Surakarta..